Development and application of diverse modelling methods to evaluate management practices for sustainable beef finishing systems in Scotland - Kamilaris, Charalampos (The University of Edinburgh, 2020)
In Scotland, cattle production is considered the main agricultural activity, with beef farmers generating the highest proportion of all Scottish agricultural revenue, mainly from the sale of animals for meat production and breeding. In addition, Scotland has the highest ratio of beef to dairy cows among the countries of the UK and Europe. However, the cattle farming sector reports consistently low or negative margins and beef farming in Scotland remains highly dependent on Common Agricultural Policy (CAP) support payments to sustain its farming activities. The beef production sector is currently faced with a volatile business environment and uncertain price conditions, which when combined with the recent global environmental concerns about the role livestock systems’ play in climate change, further compromise the robustness and future viability of the existing beef production systems. Also, beef production is recognised as an important source of greenhouse gas (GHG) emissions linked to Climate Change. As a result, widespread pressure exists for beef production systems to increase the economic and emissions efficiency of production. Various mathematical modelling attempts over the years have proven to be powerful tools tackling issues of beef production profitability and environmental concerns from numerous aspects. However, several issues impede their uptake, as the application of this knowledge to policy is hindered by the heterogeneity of agricultural systems. This thesis, therefore, set out to develop a model for the beef industry focused on the finishing stage to a) assess existing management practices to determine the drivers and limitations of profitability, b) to test scenarios to identify opportunities and alternative beef production systems in Scotland and c) to optimise these results for beef farms in Scotland. The Grange Scottish Beef Model (GSBM) was developed and customized to simulate Scottish beef finishing enterprises using data related to beef studies and agricultural input and output price datasets. The model was used to determine the cost-effectiveness of alternative management practices and slaughter ages. Results highlight the small and often negative net margins of beef finishing systems in Scotland, as well as the superior financial returns of shorter duration systems. To improve the understanding of drivers behind profitability in beef finishing systems, scenarios simulating the genetic selection of stock for feed efficiency, financial aids and optimized inter-population performance were tested. Outcomes showed better net margins than the baseline systems for all systems examined, allowing some systems to become profitable. Monte Carlo simulation was also used to provide an estimate of the effects of uncertainty surrounding carcass prices. The study also highlighted the pivotal role of management in the emissions intensity of production. Using Scotland again as a case study, the bio-economic simulation model GSBM was combined with AgRE Calc, a farm-level carbon footprinting tool, to investigate the environmental impact of a range of beef production scenarios, and trade-offs generated between mitigating emissions and increasing farm profitability. To measure the environmental impact of finishing duration, type and gender selection of beef fattening systems, emissions were grouped into five categories: (1) land and crops, (2) enteric emissions, (3) manure, (4) feed and bedding, and (5) fuel and electricity. Results suggest that more intensive shorter duration systems have the lowest environmental impact of all the systems investigated. However, medium duration pasture-based beef production systems in Scotland were found to achieve a balance between financial returns and environmental performance. Finally, a new model was developed using real-world data obtained from Scottish farms to optimise between the systems already found to be more cost-effective with simulation modelling. While policy scenarios concerning the departure of the United Kingdom from the European Union were examined to assess the future impact of policy changes on beef finishing systems in Scotland. The impacts of three post–Brexit trade scenarios that were taken from the Agri-Food and Biosciences Institute (AFBI) report on post-Brexit trade scenarios on different Scottish beef farming systems were assessed. Scenarios include a free trade agreement with the EU (FreeTrade), a deal that assumes default World Trade Organisation tariff regimes (WTO) and the Unilateral Trade Liberalisation (LibTrade), with different tariffs and market specifications applied. Results showed that even though the LibTrade scenario generated the most adverse effect to farm profitability when compared to a baseline and other post-Brexit scenarios, the most decisive factor defining the economic viability of Scottish beef farms would be the abolition of EU’s payment schemes. Together, these assessments provide a framework for the development of tools for economic and environmental analysis of beef finishing systems, intending to increase their usability and relevance. Several areas in which further progress can be made are identified, and the thesis argues for the recognition of a demand for more regionalized modelling approaches by the developers on agriculture accounting methodologies. As such, the thesis as a whole provides a detailed blueprint for the advancement of modelling livestock systems, alongside a comprehensive synthesis of the state of the art.
Keywords: beef production; cost-effectiveness; Green House Gass mitigation strategies; GHG mitigation strategies; modelling; beef production model; scottish beef finishing systems; economics of beef production; Scottish beef; simulation modelling; optimisation modelling; mathematical bio-economic model; Grange Dairy Beef Systems Model; Grange Scottish Beef Model; GSBM; GHG footprinting tool; AgRE Calc